Defining domestic water consumption based on personal water use activities - Crouch, Melissa Lauren; Heinz Erasmus Jacobs; Vanessa L. Speight (Aqua (London, England), 2021)
As the world increasingly faces water shortages, it is critical to develop realistic estimates of water consumption based on water-use activities rather than top-down imposed limits. This study quantifies the absolute basic consumption (ABC) of an individual, irrespective of water-use location or water source, with a focus on personal water-use activities rather than measured household consumption. A theoretical model to stochastically describe 21 personal water-use activities was developed, corresponding to lifestyle levels based upon Maslow's hierarchy of physiological needs. From this model, the expected value of ABC was 92 L/capita/day (LPCD) and includes restrictions on several everyday activities and thus would be better as a minimum target during stringent water restrictions. A more realistic expected value for non-wasteful, indoor-only water use was determined to be 175 LPCD. The results of this study serve as a useful benchmark to inform policy choices and efforts to conserve water without affecting health and wellbeing.